Pharmacokinetics and pharmacodynamics of rilotumumab: a decade of experience in preclinical and clinical cancer research. (26th May 2015) - Zhang, Y.; Doshi, S.; Zhu, M.
Abstract : Rilotumumab is a fully human monoclonal antibody against hepatocyte growth factor, the only known ligand of the MET receptor. Over the last decade, rilotumumab has been extensively tested in preclinical studies and in clinical studies in a variety of cancer types. In this review, we examine the pharmacokinetic and pharmacodynamic data that have been collected in the rilotumumab programme to date, and discuss retrospectively how the knowledge acquired in this programme can be applied to a number of key issues in oncology drug development, including: (i) using preclinical data to inform first‐in‐human study design; (ii) the role of biomarkers in the identification of a target patient population; (iii) the potential for drug interactions between therapeutic proteins and other anticancer agents; and (iv) pharmacokinetic and pharmacodynamic considerations in phase 3 study design.